Using carbon, nitrogen, and sulfur sourced from thiourea to co-doped TiO2 for enhanced photocatalytic degradation of rhodamine B under visible light irradiation - Le Thi Thanh Thuy; Le Thi Ca Bi (My University, 2017)
Using carbon, nitrogen, and sulfur sourced from thiourea to co-doped TiO2 for enhanced photocatalytic degradation of rhodamine B under visible light irradiation
Keywords: Co-doped TiO2